2003
DOI: 10.1117/12.488115
|View full text |Cite
|
Sign up to set email alerts
|

Potentials for high pressure/environmental SEM microscopy for photomask dimensional metrology

Abstract: Binary and phase-shifting chromium on quartz optical photomasks have been successfully investigated with high-pressure/environmental scanning electron microscopy. The successful application of this methodology to semiconductor photomask metrology is new because of the recent availability of a high-pressure SEM instrumentation equipped with high-resolution, highsignal, field emission technology in conjunction with large chamber and sample transfer capabilities. The high-pressure SEM methodology employs a gaseou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…These instruments are optimized for throughput and not resolution. In a recent paper, Postek et al (2003) showed that in laboratory instrumentation a similar detail at high accelerating voltage can be obtained; however, charging is still possible, even at the low accelerating voltages employed. Figure 5 shows a segment of a 250 nm nominal chromium line at about 140 Pa (1.1 torr) and 9 kV accelerating voltage.…”
Section: Photomask Imagingmentioning
confidence: 99%
“…These instruments are optimized for throughput and not resolution. In a recent paper, Postek et al (2003) showed that in laboratory instrumentation a similar detail at high accelerating voltage can be obtained; however, charging is still possible, even at the low accelerating voltages employed. Figure 5 shows a segment of a 250 nm nominal chromium line at about 140 Pa (1.1 torr) and 9 kV accelerating voltage.…”
Section: Photomask Imagingmentioning
confidence: 99%
“…Photomasks can be very difficult to image in the SEM due to charge build-up in the quartz. Postek et al (2003) successfully used variable pressure SEM to dissipate the charge build-up for the imaging and metrology of chromium photomasks [28]. However, as shown in Figure 10, the HIM can also be successfully employed in the imaging and metrology of these samples.…”
Section: Charge Reductionmentioning
confidence: 99%